Sequence alignment problems in bioinformatics a guided tour on algorithms and complexity Jaime Samaniego - Samaniego, Jaime M.
The field of bioinformatics relies heavily on efficient algorithms for the alignment of two or more DNA or protein sequences. This paper introduces the basic optimization problems and their variations, discusses complexity issues, and surveys some of that classic and recent alignment algorithms.
Keywords: Sequence alignment; Dynamic programming; Linear-space alignment; Wavefront parallelism; Progressive alignment